Constructing childhood : - James, Allison (Palgrave Macmillan, 2004)
This text provides a critical analysis of the social construction of childhood and children's agency. Through an interdisciplinary synthesis combining social theory, social policy and the empirical findings of social science research, it bridges the current gap between theory and practice, offering an incisive theoretical account of childhood that is grounded in substantive areas of children's lives such as health, education, crime and the family. This furthers understanding of the impact of policy on children's everyday lives and social experiences.